Lotta Poetica : numero monografico su Joseph Beuys marzo 1975 - 46. (Brescia : Studio Brescia, 1975)
Cover Designed by Joseph Beuys, This forty-sixth installment of Paul de Vree's prescient seventies art and literature periodical "Lotta Poetica" (Poetry War) is a special monographic issue devoted to Joseph Beuys. It features a cover and title page designed by the artist that is accompanied by Caroline Tisdall's photographic documentation of the 1974 piece "Three Pots Action in the Poor House".
Italiaans
Duits
Engels
boek
Keywords: Beuys, Joseph